Social perception and practices of households regarding mask use in public places during COVID-19 postquarantine period - Abhishek Singh; Ram Kumar Panika; Vikas Gupta; Pawan Kumar Goel; Rakesh Kumar Mahore; Mansi Singal (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Cases have been reported of people affected with COVID-19, facing discrimination on account of heightened fear and misinformation about infection. Hence, this global health crisis of COVID-19 pandemic offers a unique opportunity to investigate the level of perceptions and practices ??regarding the use of mask in public places among ?households of quarantined individuals following COVID-19 postquarantine period. MATERIALS AND METHODS: The study included household members of COVID-19-affected patients following postquarantine period during the 1st week of July 2020. After obtaining informed consent from 123 participants, a structured questionnaire was used to collect the data. All the tests were performed at a significance level of 5%. RESULTS: More than one-third of the participants (34.1%) were not using mask/personal protective equipment (PPE) at all in public places. Around two-third of the participants were willing to wear mask/PPE in public places such as local markets/street (64.2%), bus/train/flight (73.2%), neighborhood/institution (60.2%), and malls/shopping complex (72.4%). Only half of the study participants (50.4%) had an overall good perception score for wearing mask/PPE. CONCLUSIONS: The present study made an attempt to find the perceptions and practices of household personnel of quarantined individuals during postquarantine period regarding mask/PPE use while they are in public place, and it was observed that perception and practices were not satisfactory in this regard. The major cause might be increased stigma and violence, which might have created hesitation among them for using mask in public places. The study findings might help local administration to enhance psychological and social support.